2019
DOI: 10.1590/2179-8087.006016
|View full text |Cite
|
Sign up to set email alerts
|

Damage by Acromyrmex spp. to an Initial Pinus taeda L. Planting

Abstract: The objective of this study is to evaluate the damage caused by Acromyrmex heyeri Forel, 1899 and Acromyrmex lobicornis Emery, 1887 to Pinus taeda L. seedlings during the first two months after replanting. The experiment was conducted in the company Bosques del Plata, located in the province of Corrientes, Argentina. The evaluations were carried out at seven, 14, 21, 36, 50 and 65 days after replanting the seedlings, when the number of dead, alive, non-attacked, alive deneedled, and alive deneedled with cuts/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…LCA are considered pests because they defoliate a large number of crops of economic importance, such as coffee, cocoa, citrus, sorghum, sunflower, sugar cane, vineyards and managed forest (Anglada et al, 2013;Cantarelli et al, 2008;Cantarelli et al, 2019;Montoya-Lerma et al, 2012;Pérez et al, 2011;Sánchez-Restrepo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCA are considered pests because they defoliate a large number of crops of economic importance, such as coffee, cocoa, citrus, sorghum, sunflower, sugar cane, vineyards and managed forest (Anglada et al, 2013;Cantarelli et al, 2008;Cantarelli et al, 2019;Montoya-Lerma et al, 2012;Pérez et al, 2011;Sánchez-Restrepo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…LCA are considered pests because they defoliate a large number of crops of economic importance, such as coffee, cocoa, citrus, sorghum, sunflower, sugar cane, vineyards and managed forest (Anglada et al, 2013; Cantarelli et al, 2008; Cantarelli et al, 2019; Montoya‐Lerma et al, 2012; Pérez et al, 2011; Sánchez‐Restrepo et al, 2019). In forestry systems, Eucalyptus , Pinus , Populus and Salix plantations are the most affected by LCA (Jiménez et al, 2021; Montoya‐Lerma et al, 2012; Sánchez‐Restrepo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…planted area (896,242 ha) in Brazil (Indústria Brasileira de Árvores [IBÁ], 2020). Studies indicate that Acromyrmex lobicornis (Emery, 1888) and A. heyeri are capable of causing severe attacks on Pinus taeda seedlings at 65 days after replanting, compromising up to 20.8% of seedlings (Cantarelli, Costa, Pezzutti, Zanetti, & Fleck, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in view of the great expansion of areas with nests of leaf cutters and their "status" as pests (Cantarelli et al, 2019), coupled with the possibility that the phorids occur in Paraná, this study was undertaken to record the parasitism and the behavioral responses of leaf-cutting ants of the genus Acromyrmex to parasitic phorids, in the municipality of Londrina-PR, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Like saúvas, ants from Acromyrmex genera (Quenquéns) also affect the agricultural sector, responsible for building the largest nests, making control very difficult (Mueller et al, 2018). Studies carried out by Cantarelli et al (2019) demonstrated that Acromyrmex heyeri and Acromyrmex lobicornis are responsible for 20.8% of the losses in several Pinus taeda plantations, being attacked in the first two months after being replanted.…”
Section: Introductionmentioning
confidence: 99%